1986
DOI: 10.1002/hed.2890080408
|View full text |Cite
|
Sign up to set email alerts
|

A prospective study of shoulder disability resulting from radical and modified neck dissections

Abstract: A prospective longitudinal study of shoulder function after 103 neck dissections involving either preservation or sacrifice of the spinal accessory nerve is presented. The postoperative evolution and course of trapezius muscle denervation and resultant shoulder dysfunction were objectively determined for both radical and modified nerve sparing neck dissections. All patients were enrolled in a program of physical therapy aimed at maintaining range of motion at the shoulder joint. Shoulder function was examined … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
80
0
2

Year Published

1998
1998
2009
2009

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 136 publications
(83 citation statements)
references
References 22 publications
1
80
0
2
Order By: Relevance
“…When severing the main trunk of the accessory nerve, while scapular elevation is less likely to be affected, adduction will be slightly affected and lowering will be affected (33,34) . Remmler et al (35) reported that adduction was poor, agreeing with our findings. These data suggest that conserving not only the main trunk of the accessory nerve, but also the branches innervating the upper fibers of the trapezius muscle, is effective in preserving shoulder function, particularly scapular elevation.…”
Section: Discussion Discussion Discussionsupporting
confidence: 93%
“…When severing the main trunk of the accessory nerve, while scapular elevation is less likely to be affected, adduction will be slightly affected and lowering will be affected (33,34) . Remmler et al (35) reported that adduction was poor, agreeing with our findings. These data suggest that conserving not only the main trunk of the accessory nerve, but also the branches innervating the upper fibers of the trapezius muscle, is effective in preserving shoulder function, particularly scapular elevation.…”
Section: Discussion Discussion Discussionsupporting
confidence: 93%
“…Surgery in the posterior cervical triangle such as lymph node biopsy, benign mass excision, or radical neck dissection places the nerve at risk. Only one case of trapezius palsy in our cohort occurred secondary to radical neck dissection, which may be in part attributable to alterations in surgical techniques to preserve the spinal accessory nerve [4,33,35]. The spinal accessory nerve is also susceptible to injury from traumatic causes.…”
Section: Discussionmentioning
confidence: 81%
“…18,37 SANP results in the loss of trapezius static restraint, causing shoulder girdle depression and protraction. 6,7,15,46,53 Dynamically, trapezius dysfunction results in dramatically altered scapular kinematics and limited shoulder elevation. 7,13,14,22,46,53 Diagnosis of SANP is typically achieved by identifying associated signs such as trapezius atrophy, depressed shoulder girdle, scapular dyskinesis, trapezius weakness, and limited shoulder active abduction.…”
Section: Case Series Descriptionmentioning
confidence: 99%
“…7,13,14,22,46,53 Diagnosis of SANP is typically achieved by identifying associated signs such as trapezius atrophy, depressed shoulder girdle, scapular dyskinesis, trapezius weakness, and limited shoulder active abduction. 6,9,11,[13][14][15]28,29,31,46,48,49,53,52 Unfortunately, many of these signs are observational and unreliably recognized, which may explain a high rate of misdiagnosis. 3,4 Assessing scapular dyskinesis is unreliable.…”
Section: Case Series Descriptionmentioning
confidence: 99%
See 1 more Smart Citation